2012
DOI: 10.1177/0020764012440675
|View full text |Cite
|
Sign up to set email alerts
|

Being satisfied at work does affect burnout among psychiatrists: A national follow-up study from New Zealand

Abstract: Paying attention to aspects of job satisfaction may assist us in developing specific interventions for psychiatrists who may score high on different dimensions of burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 25 publications
2
28
0
6
Order By: Relevance
“…Poor relationships with management and supervisors have also been identified as related to burnout among psychiatry residents. However, research has found mixed results with regard to the role of job satisfaction in burnout, with some studies reporting no relationship, and other studies reporting that job satisfaction did play a role.…”
Section: Burnout In Psychiatrymentioning
confidence: 75%
“…Poor relationships with management and supervisors have also been identified as related to burnout among psychiatry residents. However, research has found mixed results with regard to the role of job satisfaction in burnout, with some studies reporting no relationship, and other studies reporting that job satisfaction did play a role.…”
Section: Burnout In Psychiatrymentioning
confidence: 75%
“…Of the included studies, 28 were quantitative, [24][25][26][27][28][29][30][33][34][35][36][37][38][39][40][44][45][46][47][48][49][50][51][52][53][54][55][56] two were qualitative, 31,32 one was interventional 41 and two had mixed methodology. 42,43 Countries of origin Studies originated from Australia, 29,40,48,55 New Zealand, 28,31,38,39 the UK, 30,34,43,47 the USA, 24,26,52 Canada, 35,50 Italy, 25,…”
Section: Methodsmentioning
confidence: 99%
“…27 Several studies involved a combination of countries 40,45,46,49 and six studies did not specify location. 32,37,41,51,53,56 Populations Twenty studies involved psychiatry doctors only, comprising psychiatrists, 25,27,31,32,[37][38][39][40][41][43][44][45]47,48,52 psychiatry trainees 35,42,55 or a combination of both. 24,49 Only three studies provided an indication of subspecialty, including child and adolescent, 36,40 adult 36 and forensic psychiatry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, OSH is a one-hour commute from Portland, where many professionals prefer to live. The greater satisfaction and decreased burnout associated with academic duties, such as teaching and scholarship (4), are lacking at OSH. Thus staff recruitment and retention have historically been difficult.…”
mentioning
confidence: 99%